PERTANGGUNGJAWABAN PIDANA TERHADAP PENGUSAHA YANG MEMBAYAR UPAH LEBIH RENDAH DARI UPAH MINIMUM (Studi Kasus Putusan Nomor 1662/PID.B/2015/PN.LBP) - Jon Nedi Piliang (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
Wage or remuneration is a problem that has never been solved until now. Wages are given as income that fulfills a decent living for workers. The government establishes a wage policy that protects workers through a minimum wage policy. The minimum wage is the minimum standard of wages by the entrepreneur to all workers based on the provisions in a certain area. The minimum wage in question has a form of conformity between the needs of a decent life by taking into account productivity and economic needs in accordance with Article 43 PP No.78 of 2015 concerning wages. What are the legal procedures and arrangements regarding the payment of wages by the entrepreneur according to the Law No. 13 of 2003 concerning employment and how is criminal responsibility for the entrepreneur who pay wages lower than the minimum wage (Case Decision No. 1662/PID.B/2015/PN.Lbp) as well as the role of the Civil Service Investigator in dealing with the problems of entrepreneurs who pay lower wages than the minimum wage.Wage procedures are based on the need for a decent living, one of them is the minimum wage setting policy by the government. Legal arrangements regarding payment of wages by the entrepreneur are regulated in Articles 88 to 98 of Law No. 13 of 2003 concerning Manpower with criminal provisions formulated in Articles 185-187 of Law No. 13 of 2003 concerning Manpower. The entrepreneurs who pay wages lower than the minimum wage in the Decision No. 1662/PID.B/2015/PN.Lbp convinced that he was guilty of violating the provisions in Article 90 paragraph (1) of Law No. 13 of 2003 concerning Manpower and had fulfilled the elements contained in Article 185 of Law No. 13 of 2003 concerning Manpower. The perpetrator is sentenced to imprisonment for 1 (one) year. The perpetrators can be held accountable for it by the reason that the perpetrator is able to take liability (physically and mentally healthy), there is an error, there is no excuse for forgiveness, the Civil Service Investigator of Manpower has the authority to resolve cases of entrepreneurs who pay wages lower than the minimum wage based on Article 182 of Law no. 13 of 2003 concerning employment. Employment Civil Servant Investigators (PPNS) must be more pro-active and professional and responsive in protecting the rights of workers/workers and judges should consider the losses incurred by workers/laborers who do not receive their salaries or rights in accordance with the minimum wage..Keywords: Criminal Liability, Entrepreneurs, Minimum Wage.